Assessing the impact of dietary choices on fiber deficiency: insights from the 2017–2020 Polish national adult nutrition survey - Kucharska, Alicja; Sińska, Beata Irena; Panczyk, Mariusz; Samel-Kowalik, Piotr; Szostak-Węgierek, Dorota; Raciborski, Filip; Samoliński, Bolesław; Traczyk, Iwona (Frontiers in Nutrition, 2024)
Introduction: Dietary fiber is a key component of a healthy diet, associated with a reduced risk of cardiovascular disease, obesity, type 2 diabetes, certain cancers, chronic inflammation, or depression. The aim of the study was to perform an in-depth analysis of dietary fiber intake in the Polish population, taking account of the consumption of groups of products that are fiber sources and identify any age-related differences in the dietary fiber intake of the subjects.We analyzed data obtained from two representative cross-sectional studies on the diet and nutritional status of adult Polish residents including the total of 4,000 individuals aged 19 years and more. Two 24-hour recalls were used per individual to assess the diet using the computer-assisted personal interview (CAPI) technique. Total fiber content and fiber contained in cereal products, vegetables, fruits, legumes, nuts and seeds were calculated. Fiber intake was compared to the recommendations: 25 g/d for adults up to 65 years of age and 20 g/d for those aged 66 years and older. All statistical analyses, including the Pearson's chi-squared test, the Student's t-test, and the Analysis of Variance (ANOVA), were conducted using STATISTICA™ version 13.3, with the results being adjusted for demographic distribution biases to enhance the representativeness.The average daily fiber intake was 17.83±0.14 g/day (78% of the recommended intake), with 20.5% of respondents meeting the requirement. More men than women (27.05% vs. 14.3%;) met the requirement and men were characterized by a higher average intake (19.34±0.20 g/day) than women (16.43±0.19 g/day). The main fiber sources were cereals (44.1%), vegetables (23.6%), and fruits (16.0%). As regards men, the sources included refined bread (25.8%), vegetables (23.1%), and fruits (10.2%) and for women, they were vegetables (24.0%), fruits (17.2%), and refined bread (16.3%). Although refined bread is not recommended as a primary fiber source due to its lower fiber content compared to whole grain bread, its high consumption significantly contributed to the total fiber intake.The prevalence of widespread dietary fiber deficiency calls for the intensification of educational efforts that address the health advantages and sources of dietary fiber, as well as methods for its inclusion in daily meals.